Urothelial carcinoma of the graft kidney with molecular analyses: a rare case report - Joyce M. Chen; G. Kenneth Haines; William Lam; Asha Reddy; Meenakshi Mehrotra; Jane Houldsworth; Qiusheng Si (BMC, 2021)
Abstract Background Malignancy after transplantation is a leading cause of death among kidney transplant recipients. However, donor-derived malignancies are rare. We report a case of a high grade papillary urothelial carcinoma arising in a transplanted kidney. Case presentation A 62-year-old female who received a kidney transplantation more than 30 years ago presented with urinary tract infection, acute renal failure, and hydronephrosis of the transplant kidney. Anterograde nephrostogram showed a large filling defect in the lower pole of the transplant kidney and in the proximal 3-4 cm of the ureter. A biopsy from the renal pelvic mass showed a high grade urothelial carcinoma. She underwent an anterior exenteration, resection of both transplant and native kidneys and bilateral pelvic lymph node dissection. Pathologic examination showed a high grade papillary urothelial carcinoma which appeared to arise in the pelvis of the graft kidney, involve the graft ureter and native urinary bladder. The tumor had metastasized to one left obturator lymph node but spared the two native kidneys and ureters. Short tandem repeat (STR) analysis confirmed the tumor to be of donor origin. Next-generation sequencing identified amplification of TERT and loss of CDKN2A/CDKN2B in the primary tumor. Conclusion While it is known that transplant recipients have an increased risk of urothelial carcinoma compared to the general population, the lack of the well-documented risk factors, such as older age at transplantation, BK polyomavirus infection, and prolonged post-transplantation history and dissemination of the tumor in this case shed light on the de novo tumorigenesis of the graft kidney within the host microenvironment. Amplification of Telomerase reverse transcriptase (TERT) and loss of cyclin dependent kinase inhibitor 2A/2B (CDKN2A/CDKN2B) detected in the tumor by next gene sequencing suggests that they may play an important role in this case.